Influence of strain rate and heat treatments on tensile and creep properties of Zn-0.15Cu-0.07Ti alloys (2016)
The use of Cu and Ti in Zn alloys improves mechanical properties as solid solution and dispersoid particles (grain refiners) may harden the material and reduce creep deformation. This is one of the main design problems for parts made with Zn alloys, even at room temperature. In this work the mechanical behavior of a Zn-Cu-Ti low alloy is presented using tensile tests at different strain rates, as well as creep tests at different loads to obtain the value of the strain rate coefficient m in samples parallel and perpendicular to the rolling direction of the Zn strip. The microstructure of the alloy in its raw state, as well as heat treated at 250°C, is also analyzed, as the banded structure produced by rolling influences the strengthening mechanisms that can be achieved through the treatment parameters.